Experimental Evaluation of the SMartyCheck Techinique for Inspecting Defects in UML Component Diagrams - Bettin, Giovanna C.; Geraldi, Ricardo Theis; OliveiraJr, Edson (Anais do Simpósio Brasileiro de Qualidade de Software (SBQS); 2018: Anais do XVII Simpósio Brasileiro de Qualidade de Software, 2018)
Software Product Line (LPS) is a paradigm that reuses software artifacts throughout a set of systems that have common and variable characteristics. To guarantee the quality of an SPL and, consequently, of its generated products, it is necessary to use verification and validation activities, such as software inspections. Thus, it is possible to detect defects in different artifacts from the earliest stages in a software development cycle. To support this activity there is a number of techniques, such as SMartyCheck, defined as a checklist-based reading technique, which allows inspection of SMarty UML diagrams. It is important to note that the SMartyCheck technique was previously evaluated in two empirical studies (one qualitative and one quantitative) taking into consideration UML use case diagrams and class diagrams. Both studies pointed out significant results in favor of SMartyCheck. SMartyCheck evolved encompassing UML component diagrams. In this sense, this paper presents initial evidence of the evaluation of SMartyCheck applied for defect detection in UML component diagram based on a controlled experiment carried out in the academy. SMartyCheck was compared to Ad Hoc inspection technique and had superior results for effectiveness and efficiency. Accuracy provided no significant difference between both techniques.